Synthesis and photovoltaic properties of thieno[3, 4‐b]pyrazine or dithieno[3′, 2′:3, 4;2″, 3″:5, 6]benzo[1, 2‐d]imidazole‐containing conjugated polymers. Issue 9 (3rd March 2015) - Keshtov, Mukhamed L.; Godovsky, Dmitri Yu.; Khokhlov, Alexei R.; Mizobe, Tetsunari; Fujita, Hiroyuki; Goto, Eisuke; Hiyoshi, Junya; Nakamura, Saki; Kawauchi, Susumu; Higashihara, Tomoya; Michinobu, Tsuyoshi
ABSTRACT: Novel conjugated polymers composed of benzo[1, 2‐ b :4, 5‐b′]dithiophene and thieno[3, 4‐ b ]pyrazine or dithieno[3′, 2′:3, 4;2″, 3″:5, 6]benzo[1, 2‐ d ]imidazole units are synthesized by Stille polycondensation. The resulting polymers display a longer wavelength absorption and well‐defined redox activities. The effective intramolecular charge‐transfer and energy levels of all polymers are elucidated by computational calculations. Bulk‐heterojunction solar cells based on these polymers as p‐type semiconductors and [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PC61 BM) as an n‐type semiconductor are fabricated, and their photovoltaic performances are for the first time evaluated. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2015, 53, 1067–1075 Abstract : Conjugated polymers composed of benzo[1, 2‐ b :4, 5‐b′]dithiophene (BDT) and thieno[3, 4‐ b ]pyrazine or dithieno[3′, 2′:3, 4;2″, 3″:5, 6]benzo[1, 2‐ d ]imidazole units, prepared by Stille polycondensation, are applied to p‐type semiconducting polymers in bulk‐heterojunction solar cells. The devices based on the polymer with the thieno[3, 4‐ b ]pyrazine unit show better photovoltaic performances than those based on the polymer with the dithieno[3′, 2′:3, 4;2″, 3″:5, 6]benzo[1, 2‐ d ]imidazole unit, probably due to the extended absorption range of the former polymer.